(untitled) (International Journal of Engineering and Computer Science, 2017)
Digital watermarking is new method of providing protection to multimedia data and digital content from unauthorized copying. Robust and imperceptible audio watermarking scheme using Discrete Wavelet Transformation (DWT) is presented in this paper. It is effective data hiding technique for audio signal. Algorithm embeds scramble watermark (image) into discrete wavelet transformed audio signal. For scrambling of image Arnold transformation based on best iteration is used. Then embedded watermark must be survived and recovered against different attacks like volume scaling, re-sampling, low pass filtering, re-quantization, random cropping